STUDI KAITAN ULTRALUMINOUS X-RAY SOURCES (ULXs) DENGAN STAR FORMATION RATE (SFR) GALAKSI INDUK - Attari Khairunnisa, Sitti
Ultraluminous X-ray Sources (ULXs) are defined as non-nuclear point-source objects with apparent X-ray luminosity exceeds the Eddington limit of a stellar mass black hole (sMBH), typically Lx > 2 x 1039 erg s-1, in the 0.3-8 keV band. ULXs are often explained with two different models: 1) ULXs as a sMBH with super-Eddington accretion or 2) ULXs as an intermediate mass black hole (IMBH) with sub-Eddington accretion. There is still no agreement on which models is the most suitable to explain ULXs, therefore further study is needed. The main goal of this Thesis is to find what kind of environment that supports the formation of ULXs. We will be focused on the correlation between the population of ULXs with properties of their host galaxies, particularly the star formation rates (SFR). The data we used were taken from a catalog that have been merged and selected by Priajana (2016) based on two catalogs from Liu (2011) and Walton et al. (2011). We did a re-selection of the ULX candidates along with their host galaxies and obtained 546 ULX candidates in 233 host galaxies. Further analysis will be focused on ULX candidates which located inside isophotal radius (R25) of their host galaxies by using inclination and position angle-corrected distance from the galactic center. From this study, we found several results, i.e., 1) interacting and starburst galaxies could trigger ULXs formation, but not a mandatory requirement, 2) many ULX candidates are suspected to be contaminants based on the inclination and position angle-corrected distance, 3) correlation between SFR and several properties of their host galaxies (Hubble type, luminosity and stellar mass) follow the general trends, 4) there are positive correlations between ULXs number and SFR for spiral, normal, peculiar, and starburst sample 5) negative trends from the specific luminosity, ULXs, and SFR distribution shows us that ULXs more likely to resides on the low-mass galaxies. This is related to high specific SFR and low metallicity that are found on low-mass host galaxies. High SFR is corresponding with the formation of the donor stars, while low-metallicity corresponds to the formation of the massive black hole.